Inkarnasi: Perwujudan Kasih Allah yang Membela, Membebaskan, dan Mengangkat Martabat Manusia - Parhusip, Parsaoran (MELINTAS An International Journal of Philosophy and Religion (MIJPR), 2019)
In Christianity, incarnation marks the culmination of the manifestation of God’s love in the world. Through the historical presence of Jesus Christ in the world, salvation is made possible. The salvation of human beings not only addresses worldly issues, but also restores their inner dignity as God’s creation. The Christian doctrine of incarnation gives hope to those who are in the situation of oppression, suffering, and injustice. The presence of Jesus Christ through the incarnation realises God’s love in defending, saving, liberating, and elevating human dignity. This article sees incarnation as  an event in which God’s act of love is experienced by human beings. This event needs to be echoed by the Church today in its mission to proclaim the Kingdom of God. The event of incarnation brings the image of the Church as God’s people who are liberated while still in pilgrimage on earth.